Are We Loving Our National Parks to Death? A Call for Research on Crime and Law Enforcement in the U.S. National Park System - Stadler, William Andrew (Criminal justice review, 2023)
Despite a recent surge of visitation and frequent media accounts of lawlessness in America’s national parks, little empirical research has been dedicated to crime and law enforcement in the U.S. national park system. The absence of systematic crime and justice research within these protected spaces should raise concern, as recent park service data and intra-agency reports suggest visitor growth, funding and personnel declines, operational shortcomings, and technology constraints may endanger the capacity of the National Park Service (NPS) to adequately address anticipated crime threats in the 21st century. This call for research aims to raise awareness of the contemporary law enforcement challenges facing this federal agency and encourage the study of crime and justice issues within the U.S. national park system. We briefly examine the evolution and current state of NPS law enforcement and its associated challenges and conclude with a conceptual road map for future research occurring in these protected spaces.